Natural History collecting and the Biogeographical tradition - Browne Janet (História, Ciências, Saúde: Manguinhos)
Great expeditions and scientific journeys carried out the collecting of Natural History material and data. Naturalists changed collected material into museum pieces, diaries, books, maps, letters and so on. As far as techniques, practices, explored areas and personnel are concerned, it becomes evident the fact that material collecting for Medicine has followed the same collecting traditions as Natural History.